EVALUATION OF SCHOOL EXCELLENCE-BASED PROMOTION STRATEGIES IN IMPROVING COMPETITIVENESS AND EDUCATIONAL QUALITY - Putri Utami, Nabila; Yulita Putri, Alifia Hesty; Rohmana, Mufdhalifatul; Sumaji, Sumaji (Universitas Muhammadiyah Ponorogo, 2024)
This study aims to assess the effectiveness of a promotional strategy focused on school excellence in improving competitiveness and educational quality at SMPN 2 Kauman. The research focuses on three main aspects: the implementation of a promotional strategy based on production excellence (art classes, tahfidz classes, achievements, and cultural events), the efficiency of digital and offline promotional channels in influencing applicant interest and the institution's image, and identifying obstacles and suggestions for improving the quality of promotion in line with the quality of educational services. This study applies a qualitative approach with a case design through interviews, observations, and document analysis. The study findings indicate that the school has consistently implemented a promotional strategy based on excellence through flagship programs and public activities that are in line with community needs. Utilizing dual promotional channels in-person through school events and online through social media has been shown to increase school appeal, although the effectiveness of digital channels still needs to be strengthened in terms of content quality and publication consistency. Key identified obstacles include limited funding, a lack of human resources trained in digital marketing, and the lack of a data-driven promotional evaluation system. Based on these findings, the study recommends strengthening school promotional management by establishing a dedicated team, planning promotions based on performance indicators, professionalizing digital content, and integrating promotions with improving the quality of educational services. This study confirms that promotional strategies that prioritize excellence and are supported by professional governance have significant potential to sustainably improve school competitiveness.